Semantic Annotation Pattern for Coding and Its Application in Component Development - Costa, Taluna Mendes d’Araujo; Santanche, Andre (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2011: Anais do V Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2011)
Source code annotations have an important role in software development. Structured annotations - those that follow building schemes - provide extra semantics to the code and are suitable for the automatization of complementary development tasks. There are recent initiatives towards interrelating annotations and ontologies, expanding their expressiveness and interoperability. In this paper we propose a new strategy based on meta-annotations to support structured annotations implicitly related to ontologies. It systematizes and simplifies the process of semantically annotating code, since programmers can use annotations without knowing details of the involved ontologies. This strategy was successfully applied in the development of components according to the Digital Content Component (DCC) model, enabling to automatize the production of semantic descriptions and interfaces for components, optimizing the development process.